2012
DOI: 10.21236/ada561020
|View full text |Cite
|
Sign up to set email alerts
|

Noise Induced Switching in Delayed Systems

Abstract: Public reporting burden for thiS cotlectton of Information Is estimated to average 1 hour per response. jncluding the time for reViewing instructions, searching existing data sources, gathering and maintaining the data needed. and completing and reviewing this collection of infonmation. Send comments regarding this burden estimate or any oUter aspect of this collection of information. including suggestions for reduCing this burden to Depanmcnt of Defense. Washington Headquarters Services. Directorate tor lnfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Such changes depend on the specifics of the individual models, and cannot be understood using the reduction described above. Precise results for large deviations in delayed Langevin equations have been obtained [30, 38]. However, the correct Langevin approximations of the models we consider here need to include delay in the diffusion term [39, 40]).…”
Section: Discussionmentioning
confidence: 99%
“…Such changes depend on the specifics of the individual models, and cannot be understood using the reduction described above. Precise results for large deviations in delayed Langevin equations have been obtained [30, 38]. However, the correct Langevin approximations of the models we consider here need to include delay in the diffusion term [39, 40]).…”
Section: Discussionmentioning
confidence: 99%
“…An extension of the approach leading to Eq. (35) to overdamped systems was compared with numerical simulations for a model system and good agreement was found in the whole range where the delay time was smaller than the relaxation time [66].…”
Section: Short Noise Correlation Timementioning
confidence: 90%
“…Schwartz et. al [44] have demonstrated that the methodology introduced in section 2 can be adapted to write this system as a Hamiltonian system,…”
Section: Time Delayed Sdesmentioning
confidence: 99%